Periodo intergenésico corto asociado a complicaciones maternas en gestantes de 18 - 35 años, en el Hospital General Martín Icaza, Babahoyo Los Ríos, periodo enero-junio 2019. - Manjarres Burgos, Wilsa Verónica (2020)
The time elapsed between the date of the last childbirth and the next pregnancy is known as the intergenic period, when this period of time is less than 24 months is considered a short intergenic period. Worldwide, around 830 women die every day due to the different maternal complications, creating a danger to the life of the newborn. The objective of this research project is to determine maternal complications due to the short intergenic period in pregnant women between 18 and 35 years of age at the General Hospital Martín Icaza, Babahoyo - Los Ríos, January - June 2019 period; A study was carried out that according to the type of research has 4 points: Applied, documentary, analytical and retrospective, the previous analysis was through the medical records using the Excel program as an instrument, a sample of approximately 406 patients attended. to the outpatient clinic of the Martin Icaza General Hospital. On the results obtained in the research project regarding age, pregnant women aged 18-20 years represented with 42% presented maternal complications more frequently; the most predominant marital status were single women with 61%; the most frequent complication was abortion with 30%; The short intergenic period that had the greatest influence was 10 - 12 months represented with 63% and in terms of contraceptive methods the high index was in those who did not use represented with 53%.